Action Dystonia in Lesch-Nyhan Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
The motor disorder associated with Lesch-Nyhan disease (LND) was studied in a total of 44 patients (ages 2 to 38 years) seen at Johns Hopkins Hospital, Baltimore, MD, and other US and international centers.